2015
DOI: 10.1002/cbic.201500322
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reconstitution of Formylglycine‐Generating Enzymes Requires Copper(I)

Abstract: Formylglycine-generating enzymes (FGEs) catalyze O2 -dependent conversion of specific cysteine residues of arylsulfatases and alkaline phosphatases into formylglycine. The ability also to introduce unique aldehyde functions into recombinant proteins makes FGEs a powerful tool for protein engineering. One limitation of this technology is poor in vitro activity of reconstituted FGEs. Although FGEs have been characterized as cofactor-free enzymes we report that the addition of one equivalent of Cu(I) increases ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…Recent work, however, showed that FGE is a copper‐dependent oxidase that might take an approach to O 2 activation and C−H cleavage similar to that of the copper‐dependent lytic polysaccharide monooxygenases (LPMOs), the peptidylglycine α‐hydroxylating monooxygenase, or dopamine/tyramine‐β‐monooxygenases . In the course of isolating the catalytic principle of FGE from T. curvata we constructed a variant in which all cysteine residues outside the active site were mutated . We converted the three buried Cys residues (187, 231, 298) into alanine and the surface‐exposed Cys284 into serine.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent work, however, showed that FGE is a copper‐dependent oxidase that might take an approach to O 2 activation and C−H cleavage similar to that of the copper‐dependent lytic polysaccharide monooxygenases (LPMOs), the peptidylglycine α‐hydroxylating monooxygenase, or dopamine/tyramine‐β‐monooxygenases . In the course of isolating the catalytic principle of FGE from T. curvata we constructed a variant in which all cysteine residues outside the active site were mutated . We converted the three buried Cys residues (187, 231, 298) into alanine and the surface‐exposed Cys284 into serine.…”
Section: Resultsmentioning
confidence: 99%
“…The proteins were produced in Escherichia coli in lysogeny broth (LB) medium at 37 °C. The catalytic activities of the purified enzymes were assayed as previously described . Each reaction mixture contained 2 μ m enzyme, 2 μ m CuSO 4 , 2 m m dithiothreitol (DTT), 50 m m EDTA, 50 m m NaCl and 50 m m Tris ⋅ HCl at pH 8.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations